2021
DOI: 10.3389/fchem.2021.757680
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Breathing Phase Transition of MOF Nanocrystallites II: Explicitly Modeling the Pressure Medium

Abstract: One of the most investigated properties of porous crystalline metal-organic frameworks (MOFs) is their potential flexibility to undergo large changes in unit cell size upon guest adsorption or other stimuli, referred to as “breathing”. Computationally, such phase transitions are usually investigated using periodic boundary conditions, where the system’s volume can be controlled directly. However, we have recently shown that important aspects like the formation of a moving interface between the open and the clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Importantly, Schmid and co-workers were able to demonstrate that direct molecular simulation of nanoscale discrete crystallites of flexible MOFs is achievable for handful of materials. , They were able to achieve these simulations by removing periodic boundary conditions and free energy sampling employing distance restraints . Moreover, to recreate realistic conditions, without using distance constraints, Schmid et al have also demonstrated an approach to capture the pressure medium . These current simulations do appear to provide a path forward for the simulation of finite-size effects, although the chemical accuracy of the description of the external crystal surface remains an important open question.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, Schmid and co-workers were able to demonstrate that direct molecular simulation of nanoscale discrete crystallites of flexible MOFs is achievable for handful of materials. , They were able to achieve these simulations by removing periodic boundary conditions and free energy sampling employing distance restraints . Moreover, to recreate realistic conditions, without using distance constraints, Schmid et al have also demonstrated an approach to capture the pressure medium . These current simulations do appear to provide a path forward for the simulation of finite-size effects, although the chemical accuracy of the description of the external crystal surface remains an important open question.…”
Section: Resultsmentioning
confidence: 99%
“…The two orders of magnitude reduction in the crystal size of ZIF-7(18)-STR in comparison to ZIF-7(12) results in a higher surface to volume ratio with a greater number of weaker surface adsorption sites causing a delay for the phase transition. This insight was motivated by the molecular simulation by Zhang et al on ZIF-8 showing that the weaker affinity of surface adsorption sites due to the lack of neighboring groups increases the activation energy barrier to initiate gate opening, requiring a larger adsorbate concentration to trigger dynamic behaviour. …”
Section: Resultsmentioning
confidence: 99%
“…The volume control method was applied to differently sized DMOF-1 and DUT-128 nanocrystallites to investigate their breathing behavior and compare it to the formerly obtained pressure bath results [18]. For this purpose, MD simulations on the FF level of the structural transition from the open to the closed pore form were performed.…”
Section: Discussionmentioning
confidence: 99%